Efficacy and safety of first- versus second-generation Bruton tyrosine kinase inhibitors in chronic lymphocytic leukemia: a systematic review and meta-analysis - Ke, Liyuan; Li, Su; Huang, Danxue; Wang, Yan (Frontiers in Pharmacology, 2024)
We conducted this first systematic review and meta-analysis to assess the competitive advantage of 2nd-generation Bruton tyrosine kinase inhibitors (BTKi) compared to 1st-generation BTKi in chronic lymphocytic leukemia (CLL). The literature search was conducted from PubMed, Web of Science, Embase databases, and hematology annual conferences. Data of over response rate (ORR), progression-free survival (PFS), and overall survival (OS) were extracted to a pool meta-analysis of efficacy; adverse events (AEs) were also extracted to a pool meta-analysis of safety. Bias risk assessment and meta-analysis were performed by Review Manager 5.3 and STATA 14 software. A total of 3649 patients from 29 cohorts were included. The results showed that the benefits of ORR and 24-month PFS in 2nd-generation BTKi compared to 1st-generation BTKi were not significant in the whole population but only in the relapsed or refractory (R/R) CLL patient subgroup (ORR: 86.4% vs. 76.2%, p = 0.013; 24-month PFS: 76.9% vs. 67.9%, p = 0.004). Any-grade AEs were comparable between 1st- and 2nd-generation BTKi, but grade 3 or higher AEs were significantly less frequent with 2nd-generation BTKi versus 1st-generation BTKi (grade 3 or higher: 53.1% vs. 72.5%; p = 0.002). Headache was more frequent with 2nd-generation BTKi, while diarrhea and atrial fibrillation were more frequent with 1st-generation BTKi. Only for patients with relapsed or refractory CLL did 2nd-generation BTKi have a competitive advantage, while adverse effects still need to be considered. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO, Identifier 42022342488.